Germantown, Smith County - Thompson, Halee (Kansas State University, The Chapman Center for Rural Studies, 2012)
The lost town of Germantown was founded by hard working settlers who, with the last of their money, bought claims on this sight. They fought valiantly to break the western Kansas landscape and began to prosper. By standing up and refusing to have a railroad they kept their quiet town, but not for long. With a town popping up four miles south next to the railway, Germantown soon faded until the only thing left was the cemetery we see today.
Halee Thompson, “Germantown, Smith County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/98.
Keywords: Anna Wagner; Germantown; Fredrick and Augusta Wagner; Middle Cedar Creek; Smith Center; Smith County